Hardware acceleration of genetic sequence alignment - Arram,J; Tsoi,KH; Luk,W; Jiang,P (2013)
Next generation DNA sequencing machines have been improving at an exceptional rate; the subsequent analysis of the generated sequenced data has become a bottleneck in current systems. This paper explores the use of reconfigurable hardware to accelerate the short read mapping problem, where the positions of millions of short DNA sequences are located relative to a known reference sequence. The proposed design comprises of an alignment processor based on a backtracking variation of the FM-index algorithm. The design represents a full solution to the short read mapping problem, capable of efficient exact and approximate alignment. We use reconfigurable hardware to accelerate the design and find that an implementation targeting the MaxWorkstation performs considerably faster and more energy efficient than current CPU and GPU based software aligners. © 2013 Springer-Verlag.